2021
DOI: 10.3390/ijms22126276
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation, Biodistribution, Toxicology and Biomonitoring of Organofluorine Compounds in Aquatic Organisms

Abstract: This review is a survey of recent advances in studies concerning the impact of poly- and perfluorinated organic compounds in aquatic organisms. After a brief introduction on poly- and perfluorinated compounds (PFCs) features, an overview of recent monitoring studies is reported illustrating ranges of recorded concentrations in water, sediments, and species. Besides presenting general concepts defining bioaccumulative potential and its indicators, the biodistribution of PFCs is described taking in consideration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 148 publications
(243 reference statements)
1
31
0
Order By: Relevance
“…The geo-accumulation index (I geo ) showed that the mangrove environment of Sungai Besar Sepang was polluted with As but relatively unpolluted (I geo < 0) for other elements in this study which is consistent with findings from prior studies in the area [32]. Bioaccumulation is the process of a chemical migrating from the external environment into the organism through all possible exposure channels, which is evaluated by a BSAF [39]. In this regard, the soft tissue 9, the Cu and Zn concentrations in the soft tissue of C. obtusa are several times greater than their concentration in the sediments.…”
Section: ■ Results and Discussionsupporting
confidence: 88%
“…The geo-accumulation index (I geo ) showed that the mangrove environment of Sungai Besar Sepang was polluted with As but relatively unpolluted (I geo < 0) for other elements in this study which is consistent with findings from prior studies in the area [32]. Bioaccumulation is the process of a chemical migrating from the external environment into the organism through all possible exposure channels, which is evaluated by a BSAF [39]. In this regard, the soft tissue 9, the Cu and Zn concentrations in the soft tissue of C. obtusa are several times greater than their concentration in the sediments.…”
Section: ■ Results and Discussionsupporting
confidence: 88%
“…The possible interaction of cocktails of environmental pollutants with pharmacological treatments, considering the interactions of absorption, metabolism, and elimination and changes in the disposition of the coadministered compounds, needs more attention. The development of new computer‐aided and artificial intelligence systems (S. Webb, 2018 ) may allow a larger scale approach to the selection of the test mixture in order to reduce the number of actual experimental tests (Chen et al., 2021 ; Lukashina et al., 2021 ; Savoca & Pace, 2021 ).…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…The bioaccumulation of these toxic substances becomes more and more dangerous, with the consumption of these substances by small animals. Once pesticided accumulate in the fatty tissues of these small animals, each successive predator will consume a large amount of toxins (Figure 7) [39]. Along the food chains, a rapid process of increasing the concentration of pollutants takes place, by bioconcentration.…”
Section: Bioaccumulation and Bioconcentrationmentioning
confidence: 99%